Morphological Structure of Rabbits Based on Body Types - Setiaji, Asep; Kurnianto, Edy; Sutopo, Sutopo; Lestari, Dela Ayu (Journal of Advanced Veterinary Research, 2023)
The study was carried out to characterize different body types of rabbits based on the phenotypic relationship between body weight and body measurements. The materials used were 135 of New Zealand Grade, 115 heads of Rex, and 60 heads of Flamish Giant. Rabbits were categorized into three groups: semi-commercial, commercial, and semi-arc body types. Pearson correlation was used to estimate the correlation coefficients between body weight and body measurements with 1% and 5% significant level. Principal component analysis (PCA) representing a linear combination of the body measurement into a factor or component was determined separately for each body type of rabbit. BW showed a significant correlation with all of the variables measured on semi-commercial and semi-arc body types. The result of PCA showed a lower factors of PC1 (-0.04 - 0.41). The highest component loaded were CD in PC3 for all body types and TB in PC2 for semi-arc body type. Chest circumference, chest depth, and chest width (chest shape) are more appropriate in predicting body weight in rabbits than body length. Body length is highly correlated with body weight, but shows low factors in the principal component analysis.Â 